2017
DOI: 10.1186/s13058-017-0890-x
|View full text |Cite
|
Sign up to set email alerts
|

Calmodulin-like protein 3 is an estrogen receptor alpha coregulator for gene expression and drug response in a SNP, estrogen, and SERM-dependent fashion

Abstract: BackgroundWe previously performed a case–control genome-wide association study in women treated with selective estrogen receptor modulators (SERMs) for breast cancer prevention and identified single nucleotide polymorphisms (SNPs) in ZNF423 as potential biomarkers for response to SERM therapy. The ZNF423rs9940645 SNP, which is approximately 200 bp away from the estrogen response elements, resulted in the SNP, estrogen, and SERM-dependent regulation of ZNF423 expression and, “downstream”, that of BRCA1.MethodsE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
29
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 34 publications
(54 reference statements)
2
29
0
Order By: Relevance
“…Based on our previous observations with respect to the modulation of ERa-ERE binding and downstream gene transcription (Ingle et al, 2013(Ingle et al, , 2016Ho et al, 2016;Liu et al, 2017;Qin et al, 2017), in the present study, we set out to test the hypothesis that SNPs hundreds of bp distant from XREs might influence AHR-XRE binding and downstream gene expression. We chose to study CYP1A1, a prototypical AHR-regulated gene, by analyzing DNA sequences across and both up and downstream of the open reading frame for putative XREs and common SNPs that mapped 6 500 bp of those XREs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Based on our previous observations with respect to the modulation of ERa-ERE binding and downstream gene transcription (Ingle et al, 2013(Ingle et al, , 2016Ho et al, 2016;Liu et al, 2017;Qin et al, 2017), in the present study, we set out to test the hypothesis that SNPs hundreds of bp distant from XREs might influence AHR-XRE binding and downstream gene expression. We chose to study CYP1A1, a prototypical AHR-regulated gene, by analyzing DNA sequences across and both up and downstream of the open reading frame for putative XREs and common SNPs that mapped 6 500 bp of those XREs.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously reported that proteins encoded by members of the testis specific Y-like (TSPYL) gene family were coregulators for the transcription of cytochrome P450s, including CYP3A4, CYP2C9, CYP2C19, CYP17A1, and CYP19A1 (Liu et al, 2013;Qin et al, 2018). Coregulators like members of the TSPYL gene family may, among other mechanisms, bind to specific DNA sequences, alter the nucleosome structure or recruit RNA polymerase, thus facilitating gene transcription (Qin et al, 2017). Therefore, changes in the binding of coregulators to DNA sequences as a result of SNPs that map hundreds of base pairs from response elements might well affect downstream gene transcription.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Obviously, this study has not resulted in an exhaustive list of AHR ligand-dependent PGx-eQTLs, but this series of experiments has provided evidence that SNPs across the genome that are at a distance from AHREs can influence AHR ligand-dependent expression. Based on the results of our previous studies, these SNPs may interact with coregulator(s) that binds to AHR to form a larger complex and may alter complex stability binding at that locus (Liu et al, 2012(Liu et al, , 2018aZhou, 2016;Ho et al, 2017;Qin et al, 2017). Future studies aimed at understanding AHR PGx-eQTLs should focus on identifying mechanisms underlying the function of these SNPs and mechanisms responsible for their cell-specific effects.…”
Section: Snps Distant From Ahres Alter Ahr-regulated Gene Expressionmentioning
confidence: 99%
“…Obviously, SNPs can create/disrupt canonical TF-binding motifs (Knight et al, 1999;Bream et al, 2002;Ingle et al, 2010), but our previous studies identified several examples of SNPs that map hundreds of base pairs (bp) distant from ligand-activated TF binding sites that could influence TF binding in a SNP genotype-by-drug exposuredependent manner (Liu et al, 2012(Liu et al, , 2018aZhou, 2016;Ho et al, 2017;Qin et al, 2017). One of those studies identified a PGx-eQTL for the aryl hydrocarbon receptor (AHR), a ligand-activated TF that is an important environmental modulator for several critical pathways and processes, including chemical toxicology, immune stimulation, cancer, and the kynurenine pathway (Stockinger et al, 2014;Liu et al, 2018b;Neavin et al, 2018).…”
Section: Introductionmentioning
confidence: 99%